The economic vulnerability of fishing households to climate change in the south Pacific region of Colombia - John Josephraj Selvaraj; Daniel Guerrero; Maria Alejandra Cifuentes-Ossa; Ángela Inés Guzmán Alvis (Heliyon, 2022)
Climate change's direct and indirect effects on marine ecosystems and coastal areas mainly impact small-scale fishers, especially in developing countries, which present extreme poverty and high dependency on marine ecosystems as a source of food and sustenance for households. Understanding the vulnerability of fishing households and considering the associated socio-economic-political complexities is essential for preserving their livelihoods and maintaining their well-being. This study proposes a measure of economic vulnerability based on the capacity of fishing households in Tumaco, located on the southern Pacific coast of Colombia, to diversify their livelihoods. Different statistical procedures have been conducted to identify the most relevant strategies in reducing the economic vulnerability of households. The results indicate that reducing the vulnerability of fishing households depends on adaptation strategies such as occupational mobility, some elements of social capital, and reduced dependence on the fisheries resource. This study could constitute an input for creating public policy that guides efforts to achieve strategies for the generation of other livelihoods and the sustainability of fishing households that continue to choose fishing as their main economic activity.